Platelet-rich plasma ameliorates lipopolysaccharide-induced cardiac injury by inflammation and ferroptosis regulation - Jiao, Yuheng; Zhang, Qingyu; Zhang, Jiayan; Zha, Yafang; Wang, Jian; Li, Yanyan; Zhang, Song (Frontiers in Pharmacology, 2022)
Sepsis-induced myocardial dysfunction (SIMD) is a fatal disease with no specific treatment worldwide to this day. As a biological product, platelet-rich plasma (PRP) has attracted much attention due to its diverse and potential biological effects. However, its role in lipopolysaccharide (LPS)-induced cardiac injury has not been fully investigated. This study aimed to explore the mechanism of PRP in SIMD. PRP (30 µL) was injected in situ into the heart, and LPS (10 mg/kg) was injected intraperitoneally into mice. Neonatal rat cardiomyocytes were treated with LPS (1 µg/mL) for 24 h. The results showed that, compared with the LPS group, PRP significantly decreased the levels of Lactate dehydrogenase (LDH) and Creatine Kinase MB (CK-MB), and improved cardiac function. In addition, PRP markedly decreased the Malonic dialdehyde (MDA) content, and increased the Superoxide dismutase (SOD) activity and Glutathione (GSH) level, demonstrating that PRP alleviated LPS-induced oxidative stress. The Western blot and qPCR results showed that LPS-induced ferroptosis and inflammation effects in vivo and in vitro were ameliorated after PRP treatment. Moreover, PRP can alleviate erastin-induced ferroptosis and improve cell viability. Mechanistically, p-AKT and p-mTOR expressions were down-regulated after treatment with LPS, while PRP pretreatment could reverse this effect. In summary, our study demonstrated that PRP could play a unique role in reducing LPS-induced cardiac injury through regulation of AKT/mTOR signaling pathways. These findings provide a new therapeutic direction for treating SIMD.